Social and Political Aspects of Physical Culture in The Soviet Union in the Years 1917-1939 - Ryszard Stefanik (Central European Journal of Sport Sciences and Medicine, 2014)
The article shows social and political aspects of implementing Soviet ideology-doctrine of physical culture after taking over the rule by communists in Russia and its evolution up to the year 1939. Physical culture, including sports was harnessed into the system of indoctrination of the population, preparation for military service and increased production effort. Sport, which was supposed to serve the working classes, became a tool of propaganda, confrontation with Western Countries and for leading politicians and trainers it became a conveyor belt of power ideology. Against the background of internal and external situation the system of so called socialistic physical culture social sport’s phenomenon was shown, which, often against the policy of authorities, remained a way of life, entertainment, and spectacle gathering many fans.